Proceso de exportación y tramitación para la asociación de pequeños productores de banano nueva era - Lima Aguirre, Ingrid Geanella (2015)
This research work is focused of finding posible needs with agricultural associations today, and one of the biggest problems is when exporting their products, which affects competition and socio economic environment of these entities; having as main objective to establish an export plan where ans transaction process is demonstrated. The integrated Project is fundamental bases the selection of scientific articles (paper) which are related to the problema to be solved, these scientific papers give us the guidelines to analyze the obstacles and barriers that may occur in the international business área.